Dynamic Optimization of Autocatalytic Esterification in a Semi‐batch Reactor. Issue 4 (17th February 2021) - Rohman, Fakhrony Sholahudin; Sata, Suhairi Abdul; Othman, Mohd Roslee; Aziz, Norashid
Abstract: Dynamic optimization of autocatalytic esterification in a semi‐batch reactor was employed to identify the most robust optimization method. Techniques such as control vector parameterization, orthogonal collocation, and multiple shooting were selected, compared, and analyzed. Three objective functions were considered, namely, maximizing conversion, minimizing final time, and maximizing operation profit using multiple input parameters, i.e., feed rate and temperature. Results from the dynamic optimization indicated that the most effective feed flow rate and temperature trajectory were demonstrated by the orthogonal collocation. The maximum conversion, minimum final time, and maximum profit from this approach were determined. Abstract : Dynamic optimization of autocatalytic esterification in a semi‐batch reactor generated the optimal feed flow rate and temperature trajectories. With the temperature profile obtained from the orthogonal collocation method, the controlled system can be driven from the initial state to a final desired state in an optimal manner, resulting in the shortest time and highest profit margin.